2023
DOI: 10.1021/acs.est.2c06077
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Occurrence and Potential Ecological Risks of Organophosphate Esters in Municipal Wastewater Treatment Plants across China

Abstract: Organophosphate esters (OPEs) discharged from wastewater treatment plants (WWTPs) have attracted increasing concerns because of their potential risks to aquatic ecosystems. The identification of the structures of OPEs is a prerequisite for subsequent assessment of their environmental impacts, which could hardly be accomplished using traditional target analytical methods. In this study, we describe the use of suspect and nontarget screening techniques for identification of organophosphate triesters and diesters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 55 publications
5
28
0
Order By: Relevance
“…Both compounds have been detected in wastewater samples. 31,35 DEGBBCPP occurred in all WWTP effluents, similar to a previous study. 31 The identifications of six aryl tri-OPEs were typically supported by the presence of characteristic fragments of monophenyl phosphate (m/z 175.01547), diphenyl phosphate (m/z 251.04677 and m/z 233.03621), or triphenyl phosphate (m/z 327.07807) (Figure S2).…”
Section: Identification Of Opcssupporting
confidence: 90%
See 1 more Smart Citation
“…Both compounds have been detected in wastewater samples. 31,35 DEGBBCPP occurred in all WWTP effluents, similar to a previous study. 31 The identifications of six aryl tri-OPEs were typically supported by the presence of characteristic fragments of monophenyl phosphate (m/z 175.01547), diphenyl phosphate (m/z 251.04677 and m/z 233.03621), or triphenyl phosphate (m/z 327.07807) (Figure S2).…”
Section: Identification Of Opcssupporting
confidence: 90%
“…Nontarget screening was performed using 14 characteristic fragments compiled from the literature 30,31,34 and identified suspect compounds (Table S4 using Xcalibur Qual Browser (Thermo Scientific) to extract MS/MS chromatograms for these characteristic fragments in each isolation window with a mass tolerance of 5 ppm. Potential precursors were identified by searching the ions in the MS spectra or MS/MS spectra within the corresponding m/z range of the isolation window.…”
Section: Screening Workflow Of Opcsmentioning
confidence: 99%
“…Most OPEs are additives rather than chemically bonded to consumer products such as textiles, building materials, and personal care products. Consequently, they are readily released via abrasion, volatilization, diffusion, or leaching, ,, posing ecological and health risks due to their endocrine-disrupting toxicities. Furthermore, the release of OPEs can be expected to intensify during recycling and reprocessing, but the source characteristics of this release remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying priority contaminants has been a pressing issue in recent years, but standardized identification methods have not yet been established. Previous studies have identified the priority contaminants in WWTPs, and surface waters based solely on ecological risk scores, , which may be inappropriate for complex environments. Therefore, besides the occurrence and ecological risks of target pollutants, their persistence and bioaccumulation capacity in the estuarine environment also need to be incorporated.…”
Section: Methodsmentioning
confidence: 99%